The Interrelation Among Course Mastery, Technology Integration Self Efficacy, and Technological Pedagogical Content Knowledge (TPACK) of Prospective Science Teachers (Universitas Negeri Semarang, 2021)
Technological Pedagogical Content Knowledge (TPACK) is an important competency that must be had by prospective teachers to realize 21st-century learning. This research was aimed to analyze the relationship and the effect of course mastery and Technology Integration Self Efficacy (TISE) on TPACK of the prospective science teachers. This research was correlation research. By using regression analysis, the relationship between course mastery and TISE was analyzed on the TPACK of the science teacher candidates. Based on the analysis, it was known that the average of course mastery, TISE, and TPACK of prospective science teachers is good enough. Meanwhile, multiple regression tests were related to the relationship between course mastery and Technology Integration Self Efficacy (TISE) on TPACK of science teacher candidates simultaneously showed a strong correlation with the correlation coefficient (R) of 0.736 and R square of 0.542. It means there is an effect of course mastery and TISE on the TPACK of the prospective science teacher by 54.20%.